Influence of daily rhythmic light spectra and intensity changes on the growth and physiological status of juvenile steelhead trout (Oncorhynchus mykiss) - Ma, Shisheng; Li, Li; Chen, Xiaoqun; Chen, Shujing; Dong, Yunwei; Gao, Qinfeng; Zhou, Yangen; Dong, Shuanglin (Frontiers in Marine Science, 2023)
The objective of this study was to investigate the effects of different rhythmic light spectra and intensities on growth performance and physiological and biochemical parameters of juvenile steelhead trout (Oncorhynchus mykiss). Seven treatments were randomly assigned to 21 tanks using a single-flow system for 13 weeks (N = 3), namely blue–purple–red light (BPR), red–purple–blue light (RPB), blue light (VB), and red light (VR). These light treatments alternated at 300, 900, and 1,200 lx, as well as a constant 900 lx of blue light (CB), red light (CR), and white light (CW). Results showed that the highest feed intake (FI), final body weight (FBW), and specific growth rate (SGR) were observed in the BPR treatment, which were significantly higher than those in the CW, CR, CB, and VB treatments. BPR treatment resulted in higher levels of insulin-like growth factor 1 (IGF-1), free triiodothyronine (FT3) and thyroxine (FT4), superoxide dismutase (SOD), and catalase (CAT), and total antioxidant capacity (T-AOC) activities were found. Fish exposed to BPR showed significantly enhanced lipase (LPS) and trypsin (Trp) activity in the stomach and gut tissues which promoted digestion. Trout exposed to a constant light spectra and intensity environment showed decreased activities of antioxidant and gastrointestinal digestive enzymes. Our results indicate the positive influence of BPR light conditions on the growth, stress response, digestion, and metabolism of juvenile steelhead trout, which is likely related to its similarity to the light rhythm in natural water environments, and can be used to improve growth and physiological status in the aquaculture trout.